Small bowel infantile hemangioma complicated with acute intestinal intussusception: A case report - Souha Laarif; Cyrine Saadi; Rabiaa Ben Abdallah; Aida Daïb; Youssef Hellal; Nejib Kaabar (Elsevier, 2023)
Introduction: Gastrointestinal hemangiomas are rare benign tumors. Melena and anemia are the main clinical but non-specific manifestations, other presentations being rare such as acute intestinal intussusception. Due to the rarity of gastrointestinal hemangiomas and the lack of specific manifestations and diagnostic methods, preoperative diagnoses are often delayed or incorrect. Case report: We report the case of a 13-week-old girl who presented with incessant crying, and bilious vomiting for 3 days. Abdominal plain X-ray revealed bowel obstruction, and ultrasonography revealed intestinal intussusception. The patient underwent immediate surgery for impairment of general condition. Surgical exploration revealed a cystic ileal lesion. A segmental resection removing the ileal lesion was performed and the final pathological findings confirmed the diagnosis of intestinal hemangioma. Conclusion: This report will provide a better understanding of the diagnosis and treatment of gastrointestinal hemangiomas.